Expression of immunohistochemical markers in non-oropharyngeal head and neck squamous cell carcinoma in Ghana - Owusu-Afriyie, O.; Owiredu, W.K.B.A.; Owusu-Danquah, K.; Larsen-Reindorf, R.; Donkor, P.; Acheampong, E.; Quayson, S.E. (PLoS ONE, 2018)
Background Head and neck cancers include carcinomas of the oral cavity, larynx, sinonasal tract and nasopharynx. Studies on molecular expression of prognostic tumour markers in Ghana are scarce. The purpose of this study was to determine the expression of p53, p16, EGFR, Cyclin-D1 and HER2 among patients with non-oropharyngeal head and neck squamous cell carcinoma (HNSCC). Methodology Tissue microarrays from 154 histologically confirmed non-oropharyngeal HNSCC at the Komfo Anokye Teaching Hospital from 2006–2014 were constructed using duplicate cores of representative and viable areas from tumours. Expression of EGFR, p53, p16, Cyclin-D1 and HER2 was evaluated using immunohistochemistry. Results For non-oropharyngeal HNSCC, majority of the cases (66.2%; 102/154) had stage IV disease. EGFR was the most expressed molecular marker (29.4%; 25/85) followed by p53 (24.0%; 29/121), p16 (18.3%; 23/126) and Cyclin-D1 (10.0%; 12/120). HER2 was not expressed in any of the cases. There was a significantly (p = 0.022) higher expression of Cyclin-D1 in tumours of the oral cavity (19.6%; 9/46) than in those of the larynx (4.7%; 2/43) and nose (3.2%; 1/31). Tumours in stages I–III were more frequently positive for p16 (28.6%; 12/42) than tumours in stage IV (13.1%; 11/84). Conclusion Expression of p53, EGFR, p16 and Cyclin-D1 in non-oropharyngeal HNSCC in Ghana is largely similar to what has been reported in published studies from other countries.